THE ROLE AND PLACE OF GERMAN SCIENCE AND RESEARCH ASSOCIATION IN GERMANY’S SCIENCE POLICY - E. A. Vodyanitskaya (Vestnik MGIMO-Universiteta)
The article describes the role and place of the German Science and Research Association (DFG) as one of the leading science support organizations in the science policy of Germany. It gives a thorough analysis of its inner structure that includes such bodies as General Assembly, Executive Committee, Senate, Joint Committee and expert boards as well as the way of their formation and scope of their powers. The legal nature of DFG as a science support organization reveals through its goals and functions stated in the Charter. They are as follows: financial support of scientific and research projects, training of young scientists, international scientific cooperation and transfer of theoretical knowledge into practice. The German Science and Research Association also stands for equal possibilities for men and women in the academic community and consults the state bodies on the science policy. The author pays particular attention to the cooperation of the organization with the state and subjects (lands), including financial issues and participation of DFG in the federal state program «Exzellenzinitiative». Moreover, the author touches a debating point of correspondence of the status of the organization to its public activity as DFG is a private law association that includes universities and other science and research institutions as its members. Finally, the article gives a comparison of the German Science and Research Association to the similar organizations in other European countries, particularly to the Danish agency on science, technology and innovation and the French National research agency. The author comes to a number of conclusions respectively the procedure of peer review and need for effective remedies to appeal the rejected project.